Understanding TAK1 deficiency in microglia: Dual mechanisms for photoreceptor protection in a mouse model of retinitis pigmentosa - Jing Zhang; Wei Yang; Jiangmei Wu; Bin Lin (Proceedings of the National Academy of Sciences, 2025)
Retinitis pigmentosa (RP) is a group of inherited retinal diseases characterized by the progressive loss of photoreceptors. Neuroinflammation has been implicated in the pathophysiology of RP and its progression. Previous studies have suggested that the transforming growth factor-beta-activated kinase 1 (TAK1) plays a pivotal role in regulating acute and chronic neuroinflammation. However, the functional role of TAK1 in neuroinflammation remains unclear in RP. Here, we observed TAK1 upregulation in activated microglia of the rd10 mouse model of RP. To create the conditional deletion of TAK1 in microglia, we backcrossed Cx3cr1 CreER/CreER mice and Tak1 fl/fl mice onto rd10 background. We found that both heterozygous (rd10;Cx3cr1 CreER/+ ;Tak1 fl/+ ) and homozygous (rd10;Cx3cr1 CreER/+ ;Tak1 fl/fl ) deletion of microglial TAK1 slowed down photoreceptor degeneration but with distinct mechanisms. The heterozygous TAK1 deficiency resulted in a reduction in the activation and proliferation of microglia and the release of proinflammatory cytokines by inhibiting STAT3 signaling. In contrast, the homozygous TAK1 deficiency induced apoptosis in microglia via the TNF/RIPK1/CASP3 signaling pathway, contributing to the reduction of microglia-mediated neurotoxicity and subsequent preservation of photoreceptors in RP. Overall, our findings highlight the crucial role of TAK1 in the survival and activation of microglia. We propose that targeting microglial TAK1, considering its expression levels and subsequent signal transduction, could offer a promising personalized therapeutic strategy for individuals with RP regardless of underlying genetic causes.